CLINICAL EFFICIENCY OF LEVOCETIRIZINE IN CHILDREN WITH SEASONAL ALLERGIC RHINITIS AND ITS IMPACT ON THE QUANTITATIVE COMPOSITION AND MORPHOLOGICAL INDICATORS OF EOSINOCYTES IN PERIPHERAL BLOOD - E.A. Ruzhitskaya; O.N. Potapova; T.V. Vinogradova; E.E. Varlamov; A.N. Pampura (Union of pediatricians of Russia, 2009)
Allergic pathology is widely spread among children. In order to perform an adequate therapy and minimize the risk of the side effects, it is essential to develop a differentiated approach of the practitioners towards the prescription of medications in view of their action on the pathological process, interaction with other medications, safety and efficiency data subject to the principles of the definitive medicine. The present article highlights the results of the clinical research of the second'generation antihistamine levocetirizine administration in the allergic rhinitis in children.Key words: allergic rhinitis, antihistamine medications, levocetirizine, action, efficiency, children.